1996
DOI: 10.1135/cccc19961662
|View full text |Cite
|
Sign up to set email alerts
|

Jatropham 5-O-β-D-Glucopyranoside from Lilium candidum L.

Abstract: Jatropham 5-O-β-D-glucopyranoside [(3-methyl-2-oxo-3-pyrroline-5-yl)-β-D-glucopyranoside] was isolated from the ethanolic extract of the petals of Lilium candidum L.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…) were prepared in the Faculty of Pharmacy, Comenius University, Bratislava, Slovak Republic. Both compounds were isolated from fresh L. candidum bulbs (Mucaji et al, ; Eisenreichová et al, ). Extraction in 96% ethanol was performed several times, followed by vacuum processing.…”
Section: Methodsmentioning
confidence: 99%
“…) were prepared in the Faculty of Pharmacy, Comenius University, Bratislava, Slovak Republic. Both compounds were isolated from fresh L. candidum bulbs (Mucaji et al, ; Eisenreichová et al, ). Extraction in 96% ethanol was performed several times, followed by vacuum processing.…”
Section: Methodsmentioning
confidence: 99%
“…Many biologically active substances were isolated from an ethanolic extract of flowers and onions of L. candidum. These are mainly flavonoids (quercetin, isorhamnetin, kaempferol) Tappi et al [8], but numerous other bioactive substances have been found in the plant: carotenoids Tappi et al [9] steroidal alkaloids, pyrrole alkaloids (lilalin, jatrophan), steroids (beta-sitosterol) and steroid saponins of furostane and spinostane type, tannins, polysaccharides, organic acids and amino acids Haladova et al [10][11][12][13][14][15][16][17][18][19]. The structural formulas of some important Lilium compounds are shown in Figure 2.…”
Section: Modern Medicinementioning
confidence: 99%